BK virus-plasmid expression vector that persists episomally in human cells and shuttles into Escherichia coli. - Milanesi, G (1984)
We describe a novel expression vector, pBK TK-1, that persists episomally in human cells that can be shuttled into bacteria. This vector includes sequences from BK virus (BKV), the thymidine kinase (TK) gene of herpes simplex virus type 1, and plasmid pML-1. TK+-transformed HeLa and 143 B cells contained predominantly full-length episomes. There were typically 20 to 40 (HeLa) and 75 to 120 143 B vector copies per cell, although some 143 B transformants contained hundreds. Low-molecular-weight DNA from TK+-transformed cells introduced into Escherichia coli were recovered as plasmids that were indistinguishable from the input vector. Removal of selective pressure had no apparent effect upon the episomal status of pBK TK-1 molecules in TK+-transformed cells. BKV T antigen may play a role in episomal replication of pBK TK-1 since this viral protein was expressed in TK+ transformants and since a plasmid that contained only the BKV origin of replication was highly amplified in BKV-transformed human cells that synthesize BKV T antigen.